Role of DNA Replication and Repair in Thymineless Death in Escherichia coli - Morganroth, Pamela A. (American Society for Microbiology, 2006)
Inhibition of DNA replication with hydroxyurea during thymine starvation of Escherichia coli shows that active DNA synthesis is not required for thymineless death (TLD). Hydroxyurea experiments and thymine starvation of lexA3 and uvrA DNA repair mutants rule out unbalanced growth, the SOS response, and nucleotide excision repair as explanations for TLD.